Catalytic application of a novel melamine–naphthalene-1, 3-disulfonic acid metal–organic framework in the synthesis of β-acetamido ketones. (30th November 2022) - Babamoradi, Jamshid; Alavinia, Sedigheh; Ghorbani-Vaghei, Ramin; Azadbakht, Reza
Abstract : We synthesized a porous multifunctional metal–organic-framework (MOF) [UiO-66-Mel-NHC10 H5 (SO3 H)2 ] based on zirconium by post-synthetic modification of UiO-66-NH2 . Abstract : We synthesized a porous multifunctional metal–organic-framework (MOF) [UiO-66-Mel-NHC10 H5 (SO3 H)2 ] based on zirconium by post-synthetic modification of UiO-66-NH2 . The obtained MOF was prepared easily by chemically attaching the cyanuric chloride and then attaching 7-amino naphthalene-1, 3-disulfonic acid on UiO-66-NH2 . Afterward, the synthesized solid was applied as a very effective multifunctional catalyst in one-pot Mannich sequences to transform aromatic aldehyde and acetophenone derivatives, acetyl chloride, and acetonitrile into β-acetamido ketone products. This technique was facile, clean, and economically justified and used only 0.01 g of the catalyst during the reaction. The easy setup, nontoxic solvent, enhanced yield, short reaction times, and high catalyst durability are among the marked benefits of this synthesis method. Furthermore, the turnover frequency was 33.3–108.8 h −1, which is comparable to values previously reported for this process. Overall, the high catalytic activity observed for UiO-66-Mel-NHC10 H5 (SO3 H)2 might be because of the obtained high surface area and the synergistic features created between Lewis acidic Zr nodes and the free Brønsted acid SO3 H groups.